PENGEMBANGAN MODEL AGROINDUSTRI BERBASIS SISTEM USAHATANI TERPADU DI WILAYAH PASANG SURUT - , Rustan Massinai, STP., M.Sc., Prof. Dr. Ir. Putu Sudira, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Integrated farming system is directed to extend the biological cycle through optimizing the utilization of by-products of agriculture and animal husbandry as well. Each link within chain cycle may then provide new product that has high economic value, so that this system is expected for empowerment and utilization of marginal land throughout the region optimally. The aims of this study were (a) to provide model of agroindustry development on the basis of compatible integrated farming systems to support agricultural development for tidal lands areas, (b) to determine several factors as support for agroindustrial region development in order to increase the performance of integrated farming economically, technical, and social communities, so that it may support farming system to empower the sustainability of farming in tidal areas, and (c) to obtain strategic formulation of agroindustry development based on integrated farming system to support support agricultural development in Pulang Pisau district. Basic study method was descriptive. Primary data collection was conducted using survey methods and interviews in Pulang Pisau district, Central Kalimantan, in May 2011 to December 2011. The develoment of model for agroindustry at tidal lands was based on condition and charactristics that specific to location. Agroindusty development at tidal lands was carried out using integrated holistic approach in which it was conducted in an integrated system with sinergy and harmony between components and sub-systems, both commodity and technology and external support as well. The result of optimization describe that land area of 2.25 hectares owned by farmers can optimize the output of integrated farming and agro-industry to support the decision of farmers for the cultivation of rice with acreage 1.89 hectares and farm production cost of Rp 850 624